Regulation of endothelial cell arrangements within hMSC – HUVEC co-cultured aggregates - Anthony J. Deegan; Wim J. Hendrikson; Alicia J. El Haj; Jeroen Rouwkema; Ying Yang (Biomedical Journal, 2019)
Background: Micro-mass culturing or cellular aggregation is an effective method used to form mineralised bone tissue. Poor core cell viability, however, is often an impeding characteristic of large micro-mass cultures, and equally for large tissue-engineered bone grafts. Because of this, efforts are being made to enhance large graft perfusion, often through pre-vascularisation, which involves the co-culture of endothelial cells and bone cells or stem cells. Methods: This study investigated the effects of different aggregation techniques and culture conditions on endothelial cell arrangements in mesenchymal stem cell and human umbilical vein endothelial cell co-cultured aggregates when endothelial cells constituted just 5%. Two different cellular aggregation techniques, i.e. suspension culture aggregation and pellet culture aggregation, were applied alongside two subsequent culturing techniques, i.e. hydrostatic loading and static culturing. Endothelial cell arrangements were assessed under such conditions to indicate potential pre-vascularisation. Results: Our study found that the suspension culture aggregates cultured under hydrostatic loading offered the best environment for enhanced endothelial cell regional arrangements, closely followed by the pellet culture aggregates cultured under hydrostatic loading, the suspension culture aggregates cultured under static conditions, and the pellet culture aggregates cultured under static conditions. Conclusions: The combination of particular aggregation techniques with dynamic culturing conditions appeared to have a synergistic effect on the cellular arrangements within the co-cultured aggregates. Keywords: Co-culture, Cellular aggregation, Pre-vascularisation, Mesenchymal stem cell, HUVEC